Critical Discourse Analysis in Media Studies: A Review Research on Its Application in Indonesian Context - Anwar, Anwar; Laraswati, Asri; Ridhani, Ridhani (Universitas Lancang Kuning, 2020)
This research examines the field of discourse analysis which has popularity in the media field and communication studies. The research is focused on the application of critical discourse analysis (CDA) in Indonesia. This study is especially interested in examining CDA’s variety of approaches. The goal of this review research is to discover and to know the role of CDA in the hidden ideologies in the media of discourse studies. The data in this study is on ten selected article journals to clarify the methods, ways, and to find in which CDA has been used in understanding social and educational phenomena. This study determined three themes in critical discourse analysis application, i.e. economic, political, and social contexts.